2012
DOI: 10.4141/cjps2011-273
|View full text |Cite
|
Sign up to set email alerts
|

Species dynamic, forage yield, and nutritive value of seeded native plant mixtures following grazing

Abstract: Schellenberg, M. P, Biligetu, B. and Iwaasa, A. D. 2012. Species dynamic, forage yield, and nutritive value of seeded native plant mixtures following grazing. Can. J. Plant Sci. 92: 699–706. There is increasing interest in native plants of North America for rangeland reseeding in the semiarid regions of western Canada. However, there is limited information available on forage yield, nutritive value and response to grazing of seeded native plant mixture. The objective of this study was to compare foliar cover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…This warm-season grass may then contribute to increasing the nutritive value of forage during the hottest periods of summer, when M. sativa was present. This result is in agreement with Schellenberg et al (2012), who showed that the inclusion of warm-season grasses in a mixture containing cool-season grasses can enhance the nutritive value of forage by increasing its protein content during late summer periods in semi-arid regions. The warmseason grass (B. gracilis) also had a higher P concentration in its tissues, when soil P was high.…”
Section: Legume Effects On Nutrient Uptake and Concentrations Of Nasupporting
confidence: 92%
See 1 more Smart Citation
“…This warm-season grass may then contribute to increasing the nutritive value of forage during the hottest periods of summer, when M. sativa was present. This result is in agreement with Schellenberg et al (2012), who showed that the inclusion of warm-season grasses in a mixture containing cool-season grasses can enhance the nutritive value of forage by increasing its protein content during late summer periods in semi-arid regions. The warmseason grass (B. gracilis) also had a higher P concentration in its tissues, when soil P was high.…”
Section: Legume Effects On Nutrient Uptake and Concentrations Of Nasupporting
confidence: 92%
“…Over time, raising cattle on pastures seeded with native grasses is sustainable and encroaches less upon neighbouring native prairies than do introduced species (Jefferson et al, 2004). Recently, several studies have indicated that seeding native species in wellmanaged systems can produce large amounts of high-quality forage for livestock grazing early, but also late, in the growing season (Jefferson et al, 2002;Schellenberg, Biligetu, & Iwaasa, 2012), as opposed to introduced species which are dormant under the dry conditions of mid-summer (Knowles, 1987). In addition, forage grasses tend to be more productive in mixture than as monocultures (Schellenberg, 2008;Tilman et al, 2001), especially when the mixtures contain both warm-and cool-season grasses.…”
Section: Introductionmentioning
confidence: 99%
“…Research found that grazing disturbance is a benefit in maintaining species diversity in re-established native grass stands and seeded native plants produced relatively stable forage under grazing over the four years 34,36 . Native grasslands have evolved under grazing and grazing can stimulate above ground production by increasing tillering and rhizome production 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the three major plant groups comprising dryland plant communities (grasses, forbs, shrubs), restoration of shrubs has proven most failure prone. When sown with grasses, shrubs often nearly or completely fail to establish (e.g., Bailey et al 2010, Fansler and Mangold 2011, Kulpa et al 2012, Schellenberg et al 2012. Consequently, ''restored'' drylands often have adequate grass stands but no shrubs or far fewer shrubs than nearby reference sites (Booth et al 1999, Simmers and Galatowitsch 2010, Frouz et al 2013.…”
Section: Introductionmentioning
confidence: 99%